Edukasi Pengelolaan Sampah Berbasis Eco enzyme untuk Mengurangi Dampak Pencemaran Lingkungan dan Resiko ISPA di Desa Karangdiyeng Kabupaten Mokokerto - Zulqaida, Salma; Indah Budhy, Theresia; Megasari, Ni Luh Ayu; Minan Zuhri, Fu’ad; Qalbani Putri, Ardhanita; Rahmawati, Annisa; Elpira, Ririn; Kristianto, Sonny; Eryna Putri, Rury (Universitas Wijaya Kusuma Surabaya, 2024)
Waste management issues and its environmental and health impacts, particularly Acute Respiratory Infections (ARI), are significant concerns in Desa Karangdiyeng, Kabupaten Mojokerto. A large portion of the community still practices waste burning, which harms both the health and the environment. This community service activity aimed to increase public awareness of environmental pollution risks from waste burning and provide training on creating eco enzymes as an eco-friendly waste management solution. The methods used included seminars on environmental pollution and ARI, as well as practical eco enzyme production training. Results showed a significant improvement in community knowledge, with an average pretest score increasing by 47.5% after attending the seminar and training. Participants were also able to practice making eco enzymes and were given plant seedlings to utilize the eco enzyme as fertilizer. This activity successfully provided benefits by raising awareness of proper waste management and its health impacts, as well as offering practical skills in eco enzyme-based waste management.